Soluble suppression of tumorigenicity 2 associated with major adverse cardiac events in children with myocarditis - Shi, Tongtong; Ge, Jing; Li, Shan; Zhang, Yali (Frontiers in Cardiovascular Medicine, 2024)
Objective Soluble suppression of tumorigenicity 2 (sST2) is associated with the prognosis of some cardiac diseases, but studies on sST2 and the prognosis of patients with myocarditis are rare. This study investigated the relationship between major adverse cardiovascular events (MACEs) and sST2 during hospitalization in pediatric patients with myocarditis. Methods This was a single-center retrospective cohort study. A total of 252 patients aged ≤14 years diagnosed with myocarditis were enrolled. Events during the hospitalization were defined as MACEs (all-cause death > new heart failure > ventricular arrhythmia). Results A total of 25 people had MACEs during their hospital stay. The mortality during hospitalization was 6/23 (26%) in patients with heart failure and 3/10 (30%) in patients with ventricular arrhythmias. After including these risk factors in a multivariate logistic regression analysis, NT-proBNP (OR 4.323; 95% CI, 2.433–7.679; p < 0.001) and sST2 (OR 1.020; 95% CI, 1.003–1.037; p = 0.022) remained statistically significant and were independent risk factors for MACEs during hospitalization in pediatric myocarditis patients. Conclusions Elevated levels of NT-proBNP and sST2 were independently associated with major adverse cardiovascular events during hospitalization in children with myocarditis, and both showed good predictive efficacy.